The Effectiveness of Improving the Performance of Teachers of Islamic Religion Education Through Teacher Certification Programs in SMA / SMK in Bogor District - Romdon Romdon; U. Supyan Sauri; Heru Sujiarto (International Journal of Nusantara Islam, 2020)
This research is motivated by the phenomenon that the effort to improve the quality of education at the senior secondary level is the teacher's performance. With good teacher quality, the learning process can take place in a quality manner, which in turn leads to quality output. One of the efforts to improve the performance of Islamic Education teachers is the provision of certification allowances for Islamic Religious Education teachers to improve their performance, which has been low so far. On the other hand, the certification of teachers for Islamic Religious Education at the SMA / SMK level is also very important, given the limited limitations of the government in appointing teachers as Civil Servants, so that the existence of teacher certification can be an alternative in an effort to improve teacher welfare. This study generally aims to obtain an overview of the certification program, implementation, evaluation, constraints and future solutions in improving the performance of SMA / SMK Islamic Religious Education teachers in Bogor Regency. The specific objectives of the study were to determine the objectives and programs, implementation, evaluation, constraints and solutions in the future to improve the performance of Islamic Education teachers of SMA / SMK in Bogor Regency through optimization of the PAI teacher certification function. This research uses a qualitative approach with a descriptive analysis method. Data collection was carried out through observation, interviews and documentation study. The results showed that the improvement of the performance of PAI SMA / SMK teachers in Bogor Regency through the teacher certification program has been implemented, and has had an optimal impact. This is shown, among others, by the level of teacher discipline in implementing learning at least 24 hours a week, being active in participating in training activities, workshops and educational seminars and improving the welfare of Islamic Education teachers. However, improving teacher performance is still constrained by both internal and external constraints. Internal constraints include low understanding, skills and motivation to carry out their main tasks and functions as educators. Meanwhile, the external obstacle is that the supervision of principals, supervisors and related agencies is still not optimal in an effort to improve teacher performance. The recommendations of this study include: the government needs to finance the implementation of the Teacher Professional Improvement program, apply strict discipline by making regulations for certified teachers, and the existence of cooperation between various parties in encouraging the teacher certification program. This is done by implementing strategic management in planning, implementing, evaluating and supervising the effectiveness of the certification program.